Bits and pieces. Food texture influences food acceptance in young children. (1st January 2015) - Werthmann, Jessica; Jansen, Anita; Havermans, Remco; Nederkoorn, Chantal; Kremers, Stef; Roefs, Anne
Highlights: A novel behavioural test for food acceptance was evaluated in young children. This behavioural test informs on which food feature influences children's intake. Variations in food texture led to reduced food intake indicative of fussy eating. Variations in food colour and food taste did not affect food acceptance. Abstract: Background: Picky or fussy eating is common in early childhood and associated with a decreased preference for a variety of foods. The aim of the current study was to test experimentally which sensory food feature influences food acceptance, which, in turn is an indication for fussy eating, in young children (32 - 48 months). Another aim was to evaluate if the behavioural measurement of food acceptance is related to parental reports of their child's fussy eating behaviour, parental feeding styles and children's BMI. Method: In a repeated-measures-design, three sensory features were manipulated separately (i.e., colour, texture and taste) while keeping the other two features constant. The baseline measurement consisted of a well-liked yoghurt, which was presented before each manipulation variant. The number of spoons that children (N = 32) consumed from each variant were registered as behavioural indication for food acceptance. Parental reports of children's eating behaviour and parental feeding styles; and children's BMI were also measured. Results: The manipulation of food texture caused a significant decrease in intake. Colour and taste manipulations of the yoghurt did not affect children's intake. Parental reports of children's fussy eating behaviour and parental feeding styles were not related to the behavioural observation of food acceptance. The behavioural measurement of food acceptance and parental accounts of fussy eating were not related to children's BMI. Conclusion: Food texture but not taste or colour alternations affected food acceptance, at least when consuming variations of a well-liked yoghurt. This knowledge is important for further research on picky-eating interventions. Parental reports of fussy eating did not concur with the behavioural observation of food acceptance. Further research is warranted to test whether these findings generalize to other food types.